Acoustic Doppler effect experiment: integration of frequency sound generator, tracker and visual analyser - Anis Nazihah Mat Daud (Tanjung Malim, 2023)
Acoustic Doppler effect experiment: integration of frequency sound generator, tracker and visual analyser by Anis Nazihah Mat Daud